2023
DOI: 10.3389/fpsyt.2023.1242611
|View full text |Cite
|
Sign up to set email alerts
|

Association between behavioral patterns and depression symptoms: dyadic interaction between couples

Qianhui Yang,
Xin Gao,
Ying Tang
et al.

Abstract: BackgroundBehavioral patterns are sometimes associated with depression symptoms; however, few studies have considered the intra-couple effects. This study examined the effect of a spouses’ behavioral patterns on depression symptoms within themself and in their spouse.MethodsA total of 61,118 childbearing age participants (30,559 husband-wife dyads) were surveyed. The depression symptoms were assessed using the nine-item Patient Health Questionnaire (PHQ-9). The behavioral patterns were identified by the latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…However, couples, as a whole, usually share a common living environment, some lifestyle and health behaviors, and emotions. Research has indicated a significant interdependence between health behaviors and depressive symptoms among partners in a couple ( Yang et al , 2023 ). Depressive symptoms in one partner significantly impact depressive symptoms in the other ( Tower and Kasl, 1995 ), which is also supported by data from our previous study ( Gan et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, couples, as a whole, usually share a common living environment, some lifestyle and health behaviors, and emotions. Research has indicated a significant interdependence between health behaviors and depressive symptoms among partners in a couple ( Yang et al , 2023 ). Depressive symptoms in one partner significantly impact depressive symptoms in the other ( Tower and Kasl, 1995 ), which is also supported by data from our previous study ( Gan et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%